Assessing the carrying capacity of Mercenaria mercenaria using a steady linear food web model in two pond‐culture ecosystems. (7th November 2022) - Feng, Jie; Zhang, Tao; Song, Hao; Yu, Zheng‐lin; Yang, Mei‐jie; Hu, Zhi; Zhou, Cong; Shi, Pu; Zhao, Wei; Zhao, Liang; Hu, Peng‐peng; Ma, Pei‐zhen; et al.
Abstract: The Ecopath model was used to construct energy flow models of two pond ecosystems: Mercenaria mercenaria –fish–halophyte polyculture and M. mercenaria monoculture. Carrying capacities (CCs) of M. mercenaria were evaluated using energy flow models. Lateolabrax maculatus and M. mercenaria showed the highest biomass in the polyculture and monoculture ecosystems, respectively, and zoobenthos represented the highest trophic levels (TLs) in both ecosystems. Energy transfer efficiency between TLs I and II, total system throughput, and primary production were significantly higher under polyculture than under monoculture. Imported food strongly affected the energy flow structure of polyculture ecosystem. The dominant food chains in the polyculture and monoculture ecosystems were detritus and predatory food chains, respectively. The ecological and production CC under polyculture (1458.84 and 1632.51 g m −2, respectively) were 10.14‐ and 8.25‐fold higher than those under monoculture (143.87 and 197.99 g m −2, respectively). Polyculture is better suited for M. mercenaria than monoculture because of higher resource utilization efficiency and M. mercenaria CC. Estimating the CC of M. mercenaria using Ecopath models can help improve the aquaculture management; however, it should be considered that the Ecopath model cannot simulate inorganic processes, so caution should be exercised while using the estimated CC‐based Ecopath model.